An ultrawide-bandwidth tapered resistive TEM horn antenna. - Li-Chung (IEEE Transactions on antennas and propagation)
A novel stable beamwidth, ultrawide-bandwidth low-scattering antenna is presented. This antenna is a modified version of the conducting slotline bowtie hybrid (SBH) antenna with resistive sheets (Rcards) introduced into the guiding structure design. Since the resistive sheets can attenuate creeping wave fields, much smaller rolled edges are needed in the Rcard SBH antenna. Moreover, due to the Rcard's partially transparent nature with respect to electromagnetic fields, the radar cross section (RCS) associated with this new antenna is smaller than the original conducting rolled edge one. By employing an optimization process based on the concept of the genetic algorithm, one can easily design the Rcard SBH antenna to obtain a very stable antenna beamwidth and phase center in both the E- and H-planes across the entire operating frequency bandwidth. Because of its constant beamwidth, low RCS, and broad-band features, the Rcard SBH antenna is an ideal antenna for many applications such as a compact range feed. Calculated and measured results are presented to demonstrate the performance of this new antenna